Johann Christoph Gottscheds Briefwechsel - Historisch-kritische Ausgabe Band 10: März 1744 - September 1745 - Gottsched, Johann Christoph (Briefwechsel, 2016)
On the occasion of the two-hundred-year anniversary of the founding of the university, the Gottsched couple traveled to Königsberg. Their journey is reflected in the letters from 1744 and 1745 along with the events of the Second Silesian War. Gottsched reports on the reception of his collection of dramatic texts Schaubüne, answers queries from academics seeking positions and acts as an intermediary between authors and publishers.